2017
DOI: 10.1002/jobm.201600710
|View full text |Cite
|
Sign up to set email alerts
|

Strain improvement of industrially important microorganisms based on resistance to toxic metabolites and abiotic stress

Abstract: Improvement of the biosynthetic capabilities of industrially relevant microbes to produce desired metabolites in higher quantities is one of the important topics of modern biotechnology. In this article, different strategies of improvement of mutated microbial strains are briefly described. This is followed by the first comprehensive review of the literature on obtaining high yielding microorganisms, that is, mutants exhibiting resistance to antimetabolites, nutritional repression, and abiotic stresses as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 178 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…To deal with toxic solutes and survive under stressful conditions, microbes have evolved a multitude of adaptive networks [110]. It has been shown that halophile-produced enzymes can be important biological substances, such as phytohormones and exopolysaccharides, which are important in plant-microbiome interactions [111].…”
Section: Microbial Bioremediation Under Abiotic Stress Conditionsmentioning
confidence: 99%
“…To deal with toxic solutes and survive under stressful conditions, microbes have evolved a multitude of adaptive networks [110]. It has been shown that halophile-produced enzymes can be important biological substances, such as phytohormones and exopolysaccharides, which are important in plant-microbiome interactions [111].…”
Section: Microbial Bioremediation Under Abiotic Stress Conditionsmentioning
confidence: 99%
“…Enhancing biosynthesis pathways that are mediated by terpenoid intermediates is limited because of their relative toxicity at high concentrations. Alternatively, mutagenesis is a classic strategy that is widely used to improve microbial industrial-candidates (Fiedurek, Trytek, & Szczodrak, 2017). In the present study, nonionizing radiation was used to activate the paclitaxel productivity in the protoplasts of Acremonium sp.…”
Section: Stimulating the Paclitaxel Production By Two Strategiesmentioning
confidence: 99%
“…In contrast to genetic engineering methods, classical mutagenesis facilitates obtaining highly efficient mutants in an easy and rapid way without specialized knowledge about microbe genomes. To obtain the required mutants, experimenters have enriched cell populations by culturing them in special environmental conditions, toxic to most cell types but less toxic or non-toxic to a desired minority of cells [24][25][26][27][28]. Induced mutation has been successfully used in a number of microbial processes (other than biotransformation) employed in the production of useful end products [27][28][29].…”
Section: Introductionmentioning
confidence: 99%